Patrolling epistemic borders in a world of borderless pandemics : epistemological policemen in COVID-19 afflicted 21st century - Nhemachena, Artwell; Makamani, Rewai; Mukesi, Munyaradzi (Langaa RPCIG, 2021)
"The global epistemological gendarmerie do not only police epistemologies but they also infect the world with infectious epidemics of laughter targeted at those people whose epistemologies are offhandedly condemned as sterile and useless in controlling and containing pandemics. Patrolling epistemic borders in ways that demobilise indigenous epistemologies, the global epistemological policemen have ironically managed to prevent "transgressive" epistemologies from crossing borders but they have fatally failed to prevent the transgressive COVID-19 from recurrently crossing borders, be they bodily, national or continental. Brandishing fetishised degree and diploma certificates, African comprador academics, who are more interested in fetishised ranks and titles than in creativity and innovation, have also fatally failed to help African communities by producing vaccines for Africans by Africans. Arguing that Eurocentric epistemologies have become sterile fetishes, the book contends that such epistemologies have disabled African scholars from actively producing vaccines on a continent where there are paradoxically more epidemics of mimetic laughter than there are efforts at creativity and innovation. The book is useful for scholars in sociology, anthropology, development studies, languages and communication, natural sciences, historical studies and social work."--